Are Middle Eastern Current Account Imbalances Excessive? - Cashin, Paul (IMF Working Papers; Working Paper ;, 2011)
Employing a dynamic panel regression, this study estimates the medium-term current account position for three subgroups of emerging market and developing countries with shared economic characteristics. The fundamental determinants of the macroeconomic balance approach to current account determination (arising from the IMF's Consultative Group on Exchange Rate (CGER)) are augmented by determinants relevant to Middle Eastern economies' current account positions. The study also assesses the deviation of the actual medium-term current account position of three Middle Eastern subgroups of countries (emerging markets; low-income and fragile economies; and net oil exporters) from their medium-term current account norms. Key findings are that: augmentation of the fundamental determinants yields plausible Middle Eastern current account norms; and in comparison with the medium-term current account norm, the actual and projected current account imbalances of each of the three subgroups are typically not excessive.